The influence of rhythm and dance to the physical fitness of children of primary school age - Голенкова, Ю. В.; Пальчук, Н. І. (Physical Education Theory and Methodology, 2014)
Objective: to determine the impact of the rhythm and choreography on physical fitness of primary school pupils. Material and methods. Analysis of pedagogical and methodological literature; interviews with experts, questionnaire; surveillance; teacher testing. Research results. The influence of rhythm and choreography means the physical fitness of primary school pupils. It is shown that the use of the lessons of physical training exercises proposed rhythm and choreography contributed to a significant improvement in women flexibility and coordination hurried abilities, and the boys - flexibility